Ultrasonographic Findings in 41 Dogs Treated with Bone Marrow Aspirate Concentrate and Platelet-Rich Plasma for a Supraspinatus Tendinopathy: A Retrospective Study - McDougall, Renee A.; Canapp, Sherman O.; Canapp, Debra A. (Frontiers in Veterinary Science, 2018)
Objective - To report sonographic findings for dogs with a supraspinatus tendinopathy (ST) treated with an ultrasound-guided intratendinous injection of bone marrow aspirate concentrate (BMAC) and platelet-rich plasma (PRP). Methods - Medical records for dogs diagnosed with a ST and treated with a BMAC-PRP injection were reviewed. Data collected included patient signalment, radiographic findings at the time of initial evaluation, and sonographic findings, including cross-sectional area (CSA), fiber pattern, and echogenicity. Results -Of 70 records reviewed, 41 met the inclusion criteria. Mean CSA of the supraspinatus tendon decreased by 0.06 cm2 between baseline and 45 days post-treatment (p= 0.0025), and 0.09 cm2 between baseline and 90 days post-treatment (p< 0.0001). Analysis of CSA in dogs with a unilateral ST at baseline revealed a difference of 0.08 cm2 between the affected and unaffected tendon at baseline, with the affected tendon measuring larger than the contralateral tendon (p< 0.0001). This difference became statistically insignificant by 45 days after treatment (u1-u0 = 0.04 cm2, p= 0.2855) and remained so 90 days post-treatment (u1-u0 = 0.03 cm2, p= 0.1910). In most cases (90.6%), the fiber pattern and echogenicity was considered improved 90 days post treatment. In a minority of these cases (13.8%) the fiber pattern and echogenicity abnormalities were considered resolved. Conclusions - Using qualitative and quantitative sonographic measures, BMAC-PRP was associated with an improvement in supraspinatus tendon size, fiber pattern, and echogenicity. Given the protracted nature of tendon healing, long-term evaluation may reveal continued improvements in chronic structural changes not captured during the current study. Functional studies are required to evaluate the clinical benefits of BMAC-PRP in the treatment of STs in dogs. Clinical significance - A ST is a common contributor to forelimb lameness in dogs and remains notoriously difficult to treat. Previous studies have been associated with inconsistent treatment outcomes. In the current study, BMAC-PRP is investigated as a minimally invasive treatment option, revealing positive sonographic results.